PARTISIPASI POLITIK DOSEN JURUSAN P.IPS FKIP UNIVERSITAS RIAU DALAM PEMILIHAN PRESIDEN 2019 - Anissa Madina Damanik; Hambali Hambali; Ahmad Eddison (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the political participation of lecturers majoring in Social Sciences Education (P.IPS) FKIP Riau University in the 2019 presidential election. Data management is performed using quantitative descriptive analysis. Samples from this study were all lecturers majoring in P-IPS FKIP Riau University as many as 44 lecturers divided into 3 departments namely Economic Education, Parallel Education and Pancasila and Citizenship Education (PPKn) with a population of 44 lecturers. The sample collection technique in this study uses the Nonprobability technique that is saturated sample or often called total sampling. According to Sugiyono (2011) the saturated sample is a sampling technique by collecting all members of the population as respondents or samples. o determine the sample size if the subject is less than 100, it is better to take all of it so that the research is population research, but if the larger subject can be taken 20-25%. So the sample in this study were all FKIP Lecturers majoring in P-IPS totaling 44 people. Complete data information in this study was obtained from Primary data and Secondary data. Data collection activities carried out by observation (observation), interviews, questionnaires and documentation. This research is descriptive in nature which aims to describe the conditions or phenomena that exist in the field, then the data obtained will be analyzed with a quantitative descriptive system with a percentage. Based on the results of research conducted, it can be concluded that overall data regarding conventional participation in the 2019 presidential election are mostly in the appropriate category (0% -50%), with the acquisition of a percentage of 32% which means "Respondents (Lecturers) have used their rights political rights according to applicable laws". And Non-Conventional Political Participation in the 2019 Presidential Election is mostly in the appropriate category (0% -50%), with a percentage gain of 3% which means "Respondents (Lecturers) have used their political rights according to applicable Laws".Key Words: Political Participation, Lecturer, Presidential Election